Development of bioactive electrospun scaffolds to support granulation tissue formation in non-healing wounds - Giacaman Fonseca, Annesi (2018)
Wound healing is a complex and coordinated response where the skin repairs itself. It can be divided into four phases: inflammation, proliferation, maturation and remodelling. The prolongation or failure of one of these phases may result in a chronic wound condition due to a healing delay or a non-healing wound. Failure of wound healing is an unsolved and significant public health problem, associated with economic and human costs. However, skin tissue regeneration may provide therapies which enhance wound healing. Despite the fact that a variety of scaffolds have been fabricated for wound healing, an increasingly aging and diabetic (as major risk factor for non-healing wounds) population is now creating a further extensive demand for new regenerative products. The first body of research examined in the present thesis evaluated the effects of propolis and its compounds, quercetin, rutin, and artepillin C on fibroblast proliferation and migration rates. In order to investigate this, cytotoxicity, membrane disruption, and in vitro scratch experiments were conducted. However, findings showed that there is not a compelling argument to pursue the use of propolis and its isolated components related to cell migration and proliferation; as a result, another natural product, Lucilia sericata maggot excretion/secretion (L. sericata maggot E/S) was investigated. The second and third bodies of research have involved the development of electrospun polycaprolactone (PCL) scaffolds in the micron scale range (2-14 µm) to allow good fibroblast infiltration. In vitro biocompatibility and infiltration behaviour of 3T3 GFP dermal fibroblasts, as an exemplar cell type on electrospun PCL scaffolds, were investigated. Additionally, synthesis of polycapolactone-poly(ethylene glycol)–block copolymer (PCL-b-PEG) was included in this study, where it was hypothesized that PCL-b-PEG containing scaffolds may enhance degradation, wettability, and cell-compatibility as previous research has reported. Caprolactone-poly(ethylene glycol) block copolymer were blended with commercial caprolactone (PCL-b-PEG/PCL) and electrospun scaffolds were developed and fully characterised. Selected scaffolds (PCL and PCL-b-PEG/PCL with an average fibre diameter of 4 μm) were compared in terms of: i) in vitro biocompatibility and cell infiltration, ii) mechanical properties, iii) physiochemical properties, iv) degradation rate, and v) porosity. The generated evidence suggested that PCL-b-PEG/PCL electrospun scaffolds with an average fibre diameter of 4 μm, with a porosity of~70% (mCT), average pore size of 40 μm and a Young’s modulus of ~9 MPa possess suitable properties to enhance the fibroblasts’ (murine and human) growth. In addition, PCL-b-PEG/PCL scaffolds allowed significantly higher fibroblast migration (60% after 5 days) compared with PCL scaffolds (40%). The third and fourth bodies of research focused on scaffolds as a platform for Lucilia sericata maggot excretion/secretion release as bioactive molecule for wound healing. The protein models (lysozyme and avidin) and the Lucilia sericata maggot excretion/secretion were absorbed onto the PCL, H-PCL and PCL-b-PEG/PCL scaffolds with and without cationic polymer poly (trimethylamino) ethyl methacrylate hydrochloride-block-Poly(N-(2-hydroxypropyl)methacrylamide (PTMAEMA33-b-PHPMA180) modification. The comparison of the release profiles of avidin from PCL, H-PCL and PCL-b-PEG/PCL scaffolds with and without out cationic polymer treatment showed that the release of avidin from cation polymer modified scaffolds, tend to exhibit zero order kinetics and is not time dependent. Meanwhile, scaffolds without cationic treatment showed a greater and prolonged burst release (first 6 h). Also, the release profile of lysozyme (smaller protein than avidin) shows that lysozyme released from PCL, H-PCL and PCL-b-PEG/PCL scaffolds without cationic polymer treatment was lower than the release from non-modified scaffolds. In addition, it was found that the bioactivity of lysozyme was not statistically reduced by the cationic modification of the scaffold surface. Finally, L. sericata maggot E/S was incorporated more efficiently on cationically modified PCL-b-PEG/PCL scaffolds than on scaffolds without cationic polymer. The loading and release of L. sericata maggot E/S from electrospun scaffolds has not been reported before. The release profiles of L. sericata maggot E/S revealed that the burst release and the cumulative release of L. sericata maggot E/S was significantly lower when cationic polymer was incorporated into the scaffolds. After 21 days, cumulative amount of released L. sericata maggot E/S was ~14 μg/mL from cationicallly modified scaffolds. No statistical differences were found between materials. In addition, the protease activity of Lucilia sericata maggot ES was preserved when PCL-b-PEG/PCL and cationically modified PCL-b-PEG/PCL scaffolds were used as release platform.